Jarosław Gara (2008). Pedagogiczne implikacje filozofii dialogu. Kraków: WAM. (Przegląd Pedagogiczny, 2013)
Recenzja publikacji: Jarosław Gara (2008). Pedagogiczne implikacje filozofii dialogu. Kraków: WAM.